INTERVENSI NON-FARMAKOLOGIS PEMENUHAN KEBUTUHAN PSIKOSOSIAL PADA LANSIA: SEBUAH KAJIAN LITERATUR - Komariah, Maria; Pratiwi, Zulfa Syafiyah; Budhiyani, Hanny; Adithia, Andi (JURNAL KEPERAWATAN MUHAMMADIYAH BENGKULU, 2021)
The physical changes that occur in the elderly are closely related to their psychosocial changes. The effects that arise due to various changes in the elderly, if not properly resolved, tend to affect the overall health of the elderly. The purpose of this literature review is to identify interventions to meet the psychosocial needs of the elderly. Researchers conducted the review and search on several search engines such as Pubmed, EBSCO. After sorting using the specified keywords, inclusion, and exclusion criteria, four articles were obtained that were appropriate and used in the literature study. The results of the literature review found several types of non-pharmacological interventions to meet the psychosocial needs of the elderly, namely horticultural therapy, physical exercise and listening to the Al-Qur'an, group work, and dance movement interventions.Â Keywords: elderly, interventions, needs, psychosocial